Maternidades e esfera pública : um estudo sobre a inserção de mães no atendimento aos adolescentes em conflito com a lei - Lira, Vilnia Batista de (2007)
The present dissertation is intended to analyze the process of organization of a group of mothers, whose main goal is defined by the compliance with the Children and Adolescents Act. The women who are members of this group, entitled Movimento Moleque (Brat Movement), faced with the repressive practices existing in the confinement units of the General Department of Social and Educational Actions (DEGASE), have taken measures in view of protecting the rights of adolescents in conflict with the Law. The mothers political participation in the social and educational care of such adolescents brings new significances into motherhood, transformed in the possibility of preserving the life of their children by means of collective and solidarity actions, other than the motherhood lived within the private enclosure of a home. In order to develop this work, I have used the methodological tools of participative observation and taken interviews with the purpose of collecting data, to provide grounds for the analysis intended. The concepts of gender and identity are used in this survey to provide grounds for analyzing motherhood, the central category in this study.